2005
DOI: 10.1111/j.1365-2265.2005.02349.x
|View full text |Cite
|
Sign up to set email alerts
|

Salivary cortisol determined by enzyme immunoassay is preferable to serum total cortisol for assessment of dynamic hypothalamic–pituitary–adrenal axis activity

Abstract: Comparisons of matched salivary and serum samples in response to dynamic hypothalamic-pituitary-adrenal (HPA) axis testing. Subjects Healthy women (n=10; three taking oral oestrogens) and men (n=2), aged 23--65 years, were recruited from the community. Measurements Paired saliva and serum samples were obtained during three protocols: 10 min of exercise at 90% of maximal heart rate (n=8), intravenous administration of corticotrophin-releasing hormone (CRH; n=4), and dexamethasone suppression (n=7). Cortisol was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
225
0
27

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 297 publications
(269 citation statements)
references
References 32 publications
(66 reference statements)
13
225
0
27
Order By: Relevance
“…This finding is supported by previous studies showing a strongly positive correlation between salivary and serum cortisol levels measured by other methods 9,10 . Salivary cortisol reflects the biologically active free form of cortisol, thereby providing a more reliable measure than serum cortisol which is an inactive bound form 2 .…”
Section: Resultssupporting
confidence: 82%
“…This finding is supported by previous studies showing a strongly positive correlation between salivary and serum cortisol levels measured by other methods 9,10 . Salivary cortisol reflects the biologically active free form of cortisol, thereby providing a more reliable measure than serum cortisol which is an inactive bound form 2 .…”
Section: Resultssupporting
confidence: 82%
“…Salivary cortisol offers several advantages: it reflects the unbound fraction of circulating cortisol, it is not influenced by saliva flow rate, and it can be collected at home, eliminating the cost of hospitalization and the stress of hospital visit (26).…”
Section: Discussionmentioning
confidence: 99%
“…It has been postulated that salivary cortisol determination is more useful, especially after ACTH stimulation test, since it refl ects immediate changes in the unbound serum cortisol without being affected by the CBG or albumin concentration. 25 It has been suggested that critically ill patients with serum free cortisol concentration Յ 2 m g/dL are at risk for adrenal insuffi ciency. 18 Using this criterion, 53% (30 of 57) of the patients by free serum cortisol and 47% (18 of 38) by salivary cortisol concentration probably have adrenal insuffi ciency.…”
Section: Discussionmentioning
confidence: 99%
“…There is enough evidence to use free serum cortisol concentration, the biologically active hormone, instead of total serum cortisol CBG reaches saturation point the increase in serum free cortisol concentrations is refl ected in salivary cortisol in a few minutes ( , 5 min), even when total serum cortisol is still low. 25 Salivary cortisol determination omits the need to measure CBG to calculate the free cortisol level, and it is less altered by changes in protein concentration.…”
Section: Discussionmentioning
confidence: 99%